Effects of peri-operative intravenous administration of dexmedetomidine on emergence agitation after general anesthesia in adults: a meta-analysis of randomized controlled trials - Zhang J; Yu Y; Miao S; Liu L; Gan S; Kang X; Zhu S (Dove Medical Press, 2019)
Jian Zhang,1,* Yang Yu,1,* Shuai Miao,2 Lu Liu,1 Shuyuan Gan,1 Xianhui Kang,1 Shengmei Zhu11Department of Anesthesiology, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital, Xuzhou Medical University, Xuzhou, China*These authors contributed equally to this workObjective: The aim of the current meta-analysis was to assess the effect of dexmedetomidine on emergence agitation (EA) and the recovery outcomes after general anesthesia in adults.Methods: We searched the PubMed, the Cochrane Central Register of Controlled Trials, Embase, Web of Science and clinicaltrials.gov for relevant randomized controlled trials (RCTs) investigating the effects of dexmedetomidine on the EA in adults after general anesthesia compared with placebo. The primary outcome was the incidence of EA. Secondary outcomes included other recovery outcomes after general anesthesia.Results: Twelve RCTs (842 participants) met the eligibility criteria. A conventional random-effects meta-analysis demonstrated that peri-operative intravenous dexmedetomidine could be effective for the prevention of EA [risk ratio (RR) 0.49, Trial Sequential Analysis (TSA)-adjusted 95% confidence interval (CI) 0.35–0.68, P<0.00001]. In addition, the TSA indicated that the meta-analysis for the incidence of EA reached the required information size (370). Lower number of patients receiving dexmedetomidine required analgesia (P=0.0009). Extubation time was longer (P=0.03) and hypotension (P=0.03) was more common with dexmedetomidine. Moreover, no difference was found in the other outcomes.Conclusion: Dexmedetomidine was shown to effectively decrease the incidence of EA and to reduce postoperative analgesic requirements. Yet, other recovery outcomes including extubation time, length of PACU stay, postoperative residual sedation, hypotension, bradycardia as well as postoperative nausea and vomiting provided no data that could be used to form final conclusions.Keywords: dexmedetomidine, emergence agitation, adults, general anesthesia, meta-analysis